Unemployment and labour market rigidities in OECD countries: the impact of taxes - Bernhard Heitger (Kiel Institute of World Economics (IfW), 2000)
This paper investigates unemployment and labour market rigidities in OECD countries in 1983?1994. The central issue is the taxation-unemployment relationship and whether this relationship is exogenous or simultaneously determined. Hausman specification tests indicate that the impact of taxation on short-term unemployment is positive and exogenous whereas the relationship between taxation and long-term unemployment is simultaneously determined. Correcting for this simultaneity results in a much higher, significant and positive regression coefficient for the impact of taxation. Thus, high taxation seems to be one of the main determinants of long-term unemployment.
Keywords: E24; 330; Unemployment; labour market institutions; taxation; Arbeitslosigkeit; Arbeitsmarkt; Steuerwirkung; OECD-Staaten